Analysis of Factors Associated with the Incidence of Stunting in Toddlers: Factor Analysis of Family Support, Health Worker Support, Insurance Participation, and Income - Kartika, Dina; Zoelkarnain, Izaak; Illiandri, Oski; Adhani, Rosihan; Musafaah, Musafaah (Newinera Publisher, 2024)
Indonesia shows a high stunting rate among middle-income countries, with the World Health Organization reporting in 2020 that 149.2 million children under five worldwide (22%) experienced stunting, and Southeast Asia contributing 30.01%. Indonesia ranks third in Southeast Asia for stunting, with an average rate of 36.4% from 2005 to 2017. In 2023, South Kalimantan reported a stunting prevalence of 24.6%, and the Liang Anggang health facility showed the highest incidence in Banjarbaru City at 20.75%, underscoring a substantial occurrence of short and very short newborns. This study conducts a bibliometric analysis of literature from 2019 to 2024 on stunting risk factors among children under five. Using Google Scholar and the Garuda Portal, relevant articles were collected and analyzed for type, citation count, origin, publisher, and year. Findings underscore several prominent risk factors, including family support, health worker assistance, insurance coverage, and income level. Four articles met the inclusion criteria and were evaluated with the Critical Appraisal Approach, focusing on stunting prevalence in toddlers; of these, two examined family support, three highlighted health worker support, and two investigated insurance's impact on stunting. All articles indicate a strong correlation between household income and stunting prevalence, suggesting low-income families are particularly vulnerable. The study recommends that Puskesmas provide comprehensive education on stunting prevention, especially targeting low-income families.